Current use of nutrition facts tables and attitudes towards new red and green front-of-package labels among Israeli consumers. (17th February 2022) - Bromberg, Michal; Sinai, Tali; Keinan-Boker, Lital; Endevelt, Ronit; Frankenthal, Dvora
Abstract: Front-of-package labels (FOPL) are designed to simplify nutrition information and to help consumers make healthier food choices. The Israeli government has implemented new regulations requiring mandatory red warning FOPL for high levels of sodium, sugar, or saturated fats. A voluntary green positive FOPL for products fitting the national nutritional recommendations was concurrently encouraged. In order to characterise adult consumers' current use of Nutrition Facts Tables (NFT) and their attitudes towards the new FOPL, a nationally representative cross-sectional telephone survey was conducted. Most of the 1, 042 survey respondents reported frequent NFT use (76.2%) and intentions to purchase fewer red-labelled (81.1%) and more green-labelled products (85.0%). Consumers with higher BMI and lower education expressed higher intentions to use the new FOPL, but not higher current use of NFT. This finding suggests that these high-risk groups, which the new labels are meant to target, may indeed benefit from the new policy.